2020
DOI: 10.21203/rs.3.rs-26923/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strategies to Overcome Vaccine Hesitancy: A Systematic Review

Abstract: Background: Vaccination, albeit a necessity in the prevention of infectious diseases, requires appropriate strategies for addressing vaccine hesitancy at an individual and community level. However, there remains a glaring scarcity of available literature in that regard. Therefore, this review aims to scrutinize globally tested interventions to increase the vaccination uptake by addressing vaccine hesitancy at various stages of these interventions across the globe and help policy makers in implementing appropri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A large survey identified low knowledge, low income, and negative attitudes of social contacts, safety concerns, and religious beliefs, as hurdles for their willingness to get vaccinated. 73 By contrast, confidence in the importance of vaccines rather than in their safety or effectiveness was shown to be the strongest determinant for vaccine uptake in a large retrospective analysis. 74 A survey in Canadian school teachers showed that those with an educational background in science or engineering, a higher general knowledge of vaccines, and belief that COVID-19 was a serious illness, were more likely to intend to receive a COVID-19 vaccine.…”
Section: Vaccine Hesitancymentioning
confidence: 95%
“…A large survey identified low knowledge, low income, and negative attitudes of social contacts, safety concerns, and religious beliefs, as hurdles for their willingness to get vaccinated. 73 By contrast, confidence in the importance of vaccines rather than in their safety or effectiveness was shown to be the strongest determinant for vaccine uptake in a large retrospective analysis. 74 A survey in Canadian school teachers showed that those with an educational background in science or engineering, a higher general knowledge of vaccines, and belief that COVID-19 was a serious illness, were more likely to intend to receive a COVID-19 vaccine.…”
Section: Vaccine Hesitancymentioning
confidence: 95%
“…Most of the research on public policies aiming to address vaccine hesitancy has focused on targeted interventions [2]. Recently in Europe, public actions fuelled hesitancy when 18 European governments suspended Vaxvevria following news reports of rare blood clots.…”
Section: Discussionmentioning
confidence: 99%
“…Most papers assessing the effectiveness of public interventions against vaccine hesitancy are generally focused on policies which target specific populations and involve interpersonal interactions. [2] provide a meta analysis of 33 studies showing that community-based interventions (generally targeting parents or caregivers of children via home visits or information campaigns through community health workers, as well as reminder interventions), monetary incentives aimed at alleviating financial constraints [3], and technology-based health literacy have significant effects. However, less is known about the effectiveness of large scale official communications about vaccine safety.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research on public policies aiming to address vaccine hesitancy has focused on targeted interventions (community-based interpersonal interactions and incentives (Singh et al, 2020)). Recently in Europe, public actions fuelled hesitancy when 18 European governments suspended Vaxvevria without coordination following news reports of rare blood clots.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies assess the effectiveness of public actions aimed at stimulating vaccine uptake. Singh et al (2020) provide a meta analysis of 33 studies of the impact of diverse public actions to encourage vaccine acceptance. They conclude that community-based interventions (generally targeting parents or caregivers of children via home visits or information campaigns through community health workers, as well as reminder interventions), monetary incentives aimed at alleviating financial constraints (Banerjee et al, 2010), and technology-based health literacy have significant effects.…”
Section: Introductionmentioning
confidence: 99%